Development and application of a pathology supported pharmacogenetic test for improved clinical management of South African patients with breast cancer and associated co-morbidities - Van der Merwe, Nicole (Stellenbosch : Stellenbosch University, 2016)
Thesis (PhD)--Stellenbosch University, 2016.